CTIM-15. RESULTS OF A PHASE IB TRIAL OF RECOMBINANT POLIO:RHINOVIRUS IMMUNOTHERAPY FOR RECURRENT PEDIATRIC HIGH GRADE GLIOMA. (14th November 2022) - Thompson, Eric; Landi, Daniel; Brown, Michael; Friedman, Henry S; McLendon, Roger; Bolognesi, Dani; Schroeder, Kristin; Becher, Oren; Friedman, Allan; Walter, Ashley; Threatt, Stevie; Jaggers, Denise; et al.
Abstract: BACKGROUND: Outcomes of recurrent pediatric high grade glioma (pHHG) are poor with a median overall survival (OS) of < 6 months. Viral immunotherapy such as the polio:rhinovirus chimera, PVSRIPO, is a novel treatment approach for recurrent pHHG. PVSRIPO is genetically engineered to prevent neurovirulence. In adults with recurrent glioblastoma treated with PVSRIPO, 21% survived > 36 months. The poliovirus receptor, CD155, is ubiquitously expressed in malignant pediatric brain tumors including pHHG. METHODS: The primary objective of this Phase 1b clinical trial was to evaluate the safety and feasibility of PVSRIPO for recurrent pHGG. PVSRIPO was given at a single dose, 5x10 7 50% tissue-culture infectious dose (TCID50 ) administered by convection enhanced delivery (CED) to children with biopsy-confirmed recurrent pHHG between ≥ 1 and ≤ 5.5 in diameter. 3 mL of PVSRIPO was delivered at 0.5 mL/hr via a single catheter. RESULTS: Eight patients were treated with PVSRIPO including 5 males and 3 females with a median age of 16.5 (range 9-19). Six patients had recurrent glioblastoma, 2 had recurrent anaplastic astrocytoma. The median number of previous recurrences prior to enrollment was 3.5 (range 1-5). Four patients received bevacizumab on-study for treatment-related peritumoral inflammation/edema. Six of 8 patients experienced 26 treatment related adverse events (AEs) possibly, probably, or definitely related to protocol treatment. There were no Grade 4 or 5 AEs. There were 3 Grade 3 AEs: 2 headaches and 1 seizure. There were no AEs related to biopsy or CED catheter insertion/removal. Median OS was 4.13 months (range 1.23-NA). One patient is currently alive at > 21 months. Monocyte and T cell inflammatory phenotypes and total CD4+ T cells were increased in peripheral blood after treatment. CONCLUSIONS: CED of PVSPRIO is both safe and feasible for the treatment of recurrent pHHG. Histologic correlative results will also be presented.